The Effect of Using Ethics Poster Media On The Disipline Of 5-6 Years Old Children At Aminah Tuzzuhriyah Kindergarten, Palembang - Desi Fitriyana; Amir Hamzah; Izza Fitri (Al-Mudarris, 2026)
This study aims to investigate the effect of using ethical poster media on improving the discipline of children aged 5–6 years at TK IT Aminah Tuzzuhriyah. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed. The participants consisted of 12 children from the El-Hakim group. Data were collected using an observation checklist and a discipline assessment rubric, supported by documentation analysis. The effectiveness of ethical poster media was analyzed through validity, reliability, normality, and homogeneity tests, followed by a t-test. The results revealed a significant difference between the pretest and posttest scores, with the pretest mean = 15 and the posttest mean = 32.3. These findings indicate an improvement in children’s discipline after the intervention. The t-test result, t(11) = 30.84, p < 0.05, further demonstrates that the use of ethical poster media has a statistically significant effect on improving discipline in early childhood. In conclusion, ethical poster media is an effective instructional medium for supporting the development of discipline in early childhood education settings.